CASE PRESENTATION: TREATMENT AND FOLLOW-UP EXPERIENCE FROM MYELODYSPLASTIC SYNDROME (MDS) REAB II TO CHRONIC MYELOMONOCYTIC LEUKEMIA (CMML) - Harika Shundo; Tuba Öztoprak (Hematology, Transfusion and Cell Therapy)
Objective: The purpose of this case presentation is to discuss the clinical course, pathological findings, and treatment process of a patient diagnosed with MDS REAB II. It examines the transformation to CMML under the treatment of Venetoclax + Azacitidine. Challenges encountered during the follow-up process of CMML are mentioned. By addressing the continuation of MDS REAB II treatment in CMML, it is aimed that the findings obtained from this case contribute to the diagnostic and treatment processes for similar patients. Case Report: A 79-year-old male patient was found to have anemia, thrombocytopenia, and leukocytosis in the hemogram. Atypical cells were observed in the peripheral smear. The patient had lost 8 kg in the last 3 months and experienced night sweats. His medical history includes prostate cancer and heart diseases. Abdominal tomography revealed hepatomegaly and splenomegaly.At presentation: WBC - 16.12 × 10^3/uL; absolute monocyte count (MONO) - 3.61 × 10^3/uL; Hemoglobin (HGB) - 9.1 g/dL; Hematocrit (HTC) - 29.5%; Mean corpuscular volume (MCV) - 94.9 fL; Platelet (PLT) - 129 × 10^3/uL; Creatinine - 1.27 mg/dL; Lactate Dehydrogenase (LDH) - 340 U/L; eGFR - 67 mL/min/1.73 m²; Albumin - 3.5 g/dL; Total Protein - 7.9 g/dL; Ferritin - 171.42 µg/L; Folate - 16.9 µg/L; B12 - 353 ng/L. Anti-HBc IgG: (+), HBsAg: (-), Anti-HCV: (-), Anti-HIV: (-).On 09/02/2024, the bone marrow pathology result showed an increase in blasts, leading to the diagnosis of MDS REAB-II. Flow cytometry revealed an 11.1% blast rate in the bone marrow. Treatment with Venetoclax and Azacitidine was initiated for MDS REAB-II.After 4 cycles, follow-up results showed: WBC - 16.38 × 10^3/uL; MONO - 3.54 × 10^3/uL; HGB - 11.6 g/dL; HTC - 35.7%; MCV - 90.4 fL; PLT - 110 × 10^3/uL; Creatinine - 1.27 mg/dL; LDH - 257 U/L. Due to ongoing bicytopenia and for treatment response evaluation, a biopsy performed on 24/07/2024 revealed findings consistent with CMML without an increase in blasts. An off-label application was made for the continuation of current treatment.The effectiveness of the combination of Venetoclax and Azacitidine in the treatment of CMML is also being investigated, with the goal of monitoring the patient with the current treatment. Methodology: On December 6, 2023, the patient underwent surgery after preoperative severe anemia and thrombocytopenia, requiring blood transfusions. After discharge, the patient was referred to the hematology outpatient clinic. A bone marrow biopsy was planned due to atypical cells observed in the peripheral smear related to bicytopenia, which was sent for pathology and flow cytometry studies. Results: Abdominal tomography revealed: liver size increased to 165 mm, with millimetric parenchymal calcifications observed in the liver dome; spleen size increased to 141 mm.On 22/01/2024, pathology results showed MDS REAB II with increased blasts. Flow cytometry indicated a blast rate of 11.1% (CD13/CD117/CD34). Such findings are typically observed in cases favoring ''MDS.''After 4 cycles of Venetoclax and Azacitidine treatment, a repeat biopsy on 24/07/2024 showed results indicating RAEB-II type MDS. The bone marrow was sampled regarding blast percentage. It is unclear if the patient has been treated recently. Peripheral blood reports indicate relative (30.7%) and absolute (2.97 k/uL) monocytosis, normochromic normocytic anemia, and thrombocytopenia.With absolute (2.97 k/uL) and relative (30%) monocytosis present; the hypercellular bone marrow (%60) represents slight maturation anomalies compatible with CMML-I, and no blast increase was detected. Conclusion: The challenges in diagnosing and treating CMML arise from the coexistence of dysplasia and myeloproliferative features. According to World Health Organization criteria, the diagnostic criteria have been met considering the patient's condition. For the first time in this case, a transition from MDS REAB II to CMML has been observed under this treatment. Azacitidine and Decitabine, approved for the treatment of MDS, have also been approved for CMML patients. Furthermore, more advanced studies are underway regarding the effectiveness of Azacitidine and Decitabine in CMML treatment. The effectiveness of the combination of Venetoclax and Azacitidine is also being investigated, with the goal of monitoring the patient with the current treatment.